A-285 Malingering of Executive Function in Traumatic Brain Injury. (17th August 2022) - Revels-Strother, Olivia; Suhr, Julie
Abstract: Objective: The current study explored whether the Delis-Kaplin Executive Functioning System (D-KEFS) Stroop test and Barkley Deficits in Executive Function System (BDEFS) measure are vulnerable to malingering and whether cutoffs on each could be identified to detect malingering. Method: Using a simulator design, students recruited from the psychology participant pool at Ohio University (Mage=21.20, SD=5.85; 77.3% white, 52% freshmen, 68% assigned female, 12% prior ADHD diagnosis, 20% history of mild TBI, and 38.7% current psychological diagnoses) were randomly assigned to either malinger (simulator condition) Traumatic Brain Injury or perform normally (control condition). Participants were virtually administered the Test of Pre-Morbid Functioning, the D-KEFS, Test of Memory Malingering, and BDEFS. They also completed Qualtrics adherence items. Participants were excluded based on their Qualtrics response and for insufficient data. Results: As hypothesized, malingerers scored worse than controls on both measures. The Inhibition subtest (both raw and scaled scores) of the D-KEFS Stroop discriminated simulators from controls and a cutoff for the raw score was identified that detected 48% of simulators, with 90% specificity. The BDEFS total score also discriminated malingerers from controls, and a cutoff was identified that detected 56% of simulators, with 90% specificity. Supplemental chi square analysis showed poor congruence between the two measures, p=.262. Conclusions: The present study provides support for the potential utility of the D-KEFS Inhibition raw scores and BDEFS total scores as indicators of malingered executive functioning in TBI. Overall, results support the need to include both Performance Validity Tests and Symptom Validity Tests in assessment.